The origins and early establishment of two colonial schools - King, Ruby Hope
This paper traces the early development of Queen's College, Guyana and Jamaica College. It presents an overview of significant developments in education up to the time, and compares the underlying goals and purposes of their respective founding fathers, as well as their roles in the establishment of the schools, within the contemporary socio-political context
Keywords: Queen's College